Holter Monitor Rhythm Parameters in Healthy Infants, Children, and Adolescents: Defining Reference Limits With Meta‐Analysis - James J. Joyce; Soujanya Bogarapu; Collins Odhiambo; Sunita J. Ferns; Harold L. Kennedy (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Ambulatory electrocardiography has been in clinical use for 5 decades. However, reference limits for rhythm parameters in healthy infants, children, and adolescents have not been adequately defined. We sought to determine these reference ranges using meta‐analysis of existing published studies of 24‐hour Holter monitoring in healthy pediatric populations. Methods Multiple literature databases were searched from 1969 to May 2024 for relevant studies. Data extraction and analysis were completed according to the Meta‐Analysis of Observational Studies in Epidemiology guidelines. The prevalence of cardiac ectopy and conduction delays along with mean±SD of heart rates were obtained and grouped by the following age ranges: neonates (birth to 4 weeks), older infants (1–12 months), younger children (1–6 years), older children (7–12 years), and adolescents (13–18 years). Ninety‐five percent reference ranges for all rhythm variables were estimated in each age group. Results Forty‐five studies including 3886 participants were identified and analyzed. Minimum, average, and maximum heart rates during Holter monitoring decreased with age as expected. Prevalence of transient first‐degree atrioventricular block and Wenckebach second‐degree atrioventricular block increased with age to around 14% in adolescence. Prevalence rates for any premature atrial complexes and premature ventricular complexes were also highest in adolescence at 50% and 29%, respectively. The upper limits for the number of premature atrial complexes per day were 150 in infants and 50 in the older age groups and for premature ventricular complexes were 50 in all age groups. Conclusions Holter monitor age‐related reference limits for healthy infants, children, and adolescents are proposed.